Potret Pendidikan di Indonesia: Pandangan dan Peran Pendidik Kristen - Asmat Purba; Martin L Manao; Alon Mandimpu Nainggolan (Peneliti.net, 2022)
The purpose of this article is to present and awaken Christian educators to be able to see and improve the implementation of education in Indonesia, which still has a number of problems, including low teacher quality, a school environment that is not child-friendly, and discrimination against persons with disabilities. Christian educators must have passion in their duties as educators. If students experience rejection, mental stress, and other violence, Christian educators are expected to heal them. This research is qualitative, looking for phenomenal information through online newspapers to obtain data by reducing certain data and sorting according to the research objectives so that conclusions can be drawn.